Xeno-Fungusphere: Fungal-Enhanced Microbial Fuel Cells for Agricultural Remediation with a Focus on Medicinal Plants - Da-Cheng Hao; Xuanqi Li; Yaoxuan Wang; Jie Li; Chengxun Li; Peigen Xiao (Agronomy)
The xeno-fungusphere, a novel microbial ecosystem formed by integrating exogenous fungi, indigenous soil microbiota, and electroactive microorganisms within microbial fuel cells (MFCs), offers a transformative approach for agricultural remediation and medicinal plant conservation. By leveraging fungal enzymatic versatility (e.g., laccases, cytochrome P450s) and conductive hyphae, this system achieves dual benefits. First, it enables efficient degradation of recalcitrant agrochemicals, such as haloxyfop-P, with a removal efficiency of 97.9% (vs. 72.4% by fungi alone) and a 27.6% reduction in activation energy. This is driven by a bioelectric field (0.2–0.5 V/cm), which enhances enzymatic activity and accelerates electron transfer. Second, it generates bioelectricity, up to 9.3 μW/cm2, demonstrating real-world applicability. In medicinal plant soils, xeno-fungusphere MFCs restore soil health by stabilizing the pH, enriching dehydrogenase activity, and promoting nutrient cycling, thereby mitigating agrochemical-induced inhibition of secondary metabolite synthesis (e.g., ginsenosides, taxol). Field trials show 97.9% herbicide removal in 60 days, outperforming conventional methods. Innovations, such as adaptive electrodes, engineered strains, and phytoremediation-integrated systems, have been used to address soil and fungal limitations. This technology bridges sustainable agriculture and bioenergy recovery, offering the dual benefits of soil detoxification and enhanced crop quality. Future IoT-enabled monitoring and circular economy integration promise scalable, precision-based applications for global agroecological resilience.